Culturally Responsive Community-Based Inquiry to Enhance Basic Scientific Literacy in Indigenous Papua Border Elementary Schools - Aisyah Ali; Akhmad Kadir; Ria Ristiani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study investigates the effectiveness of a community-based, culturally responsive science learning model in improving basic scientific literacy among elementary students in the Indonesia–Papua New Guinea border region. The research addresses the persistent problem of low scientific literacy, which is largely caused by instructional practices that overlook the ecological and cultural contexts of Indigenous Papuan communities. Using a one-group pretest–posttest design, the study involved 89 students from three Indigenous community schools. A culturally adapted 12-item instrument was employed to assess five dimensions of scientific literacy: conceptual knowledge, scientific processes, scientific ethics, attitudes toward science, and scientific behaviors. Data were analyzed using Shapiro–Wilk tests, paired t-tests or Wilcoxon signed-rank tests, N-Gain scores, and effect sizes. Results demonstrated statistically significant improvements across all dimensions (p < 0.001). N-Gain values ranged from 0.31 to 0.36, indicating moderate learning gains, while effect sizes fell within the small-to-moderate range. These findings show that integrating local ecological practices—particularly through sago-based inquiry activities—and involving Indigenous community members meaningfully enhanced students’ engagement, conceptual understanding, and reflective scientific behaviors. The study concludes that a culturally grounded community-based instructional approach contributes to more equitable, contextually relevant, and sustainable science education in Indigenous and borderland school settings.